Evaluation Quality and Success Implementation of Nganjuk Smart City Mobile Application Using Technology Acceptance Model (TAM) and Delone Mclean Model Approach - Anisya, Rossa Dini; Herlambang, Admaja Dwi; Rachmadi, Aditya (Journal of Information Technology and Computer Science, 2021)
Nganjuk Smart City is an android-based mobile application that was created to help Nganjuk citizen obtain public information and services. This research uses Technology Acceptance Model (TAM) and Delone & Mclean in order to determine quality and success implementation condition of Nganjuk Smart City. Data retrieval was conducted by sharing online and offline questionnaires to 175 respondents and used purposive sampling techniques to determine research samples. The result of this research is quality condition implementation of Nganjuk Smart City based on Technology Acceptance Model (TAM) falls into high category and get 71.4% score, while successful condition implementation of Nganjuk Smart City based on Delone & McLean model falls into the high category and get 69.4% score. There are 4 variables and 18 indicators that get improvement recommendations because they get scores lower than the total average scores.